A Cassava vein mosaic virus promoter cassette induces high and stable gene expression in clonally propagated transgenic cassava (Manihot esculenta Crantz) - Oyelakin, O.O.; Opabode, J.T.; Raji, A.A.; Ingelbrecht, I.L. (Elsevier, 2015)
The study described a T-DNA vectorwith a Cassava veinmosaic virus promoter cassette (pCsVMV) and a kanamycin selectable marker gene driven by the 35S Cauliflower mosaic virus promoter with a view to stably express transgenes over repeated cycles of clonal propagation. A ?-glucuronidase reporter gene under control of pCsVMV (pCsVMV-GUS) was introduced into the cassava landrace ‘Tokunbo’ via Agrobacterium-mediated genetic transformation. Transgenic tobacco plants (Nicotiana tabacumSR1) with the same gene construct were also produced. In tobacco, the pCsVMV-GUS was highly expressed in all tissues tested such as leaf, stem, petiole, and roots. In transgenic cassava, the pCsVMV-GUS gene was highly expressed in all tissues and most cell types of in vitro plants including leaf, stem, petiole, and fibrous roots. The pCsVMV-GUS gene was also highly expressed in these tissues as well as in tubers of greenhouse grown cassava. High and stable pCsVMV-GUS gene expression wasmaintained over 3 cycles of ratooning under greenhouse conditions, thus showing the absence of undesired gene silencing effects after repeated in vitro subculturing and vegetative propagation. Fromthe high constitutive levels of GUS activity observed, the study concluded that the CsVMV promoter cassette was useful for high-level expression in cassava over repeated cycles of clonal propagationThe study described a T-DNA vectorwith a Cassava veinmosaic virus promoter cassette (pCsVMV) and a kanamycin selectable marker gene driven by the 35S Cauliflower mosaic virus promoter with a view to stably express transgenes over repeated cycles of clonal propagation. A ?-glucuronidase reporter gene under control of pCsVMV (pCsVMV-GUS) was introduced into the cassava landrace ‘Tokunbo’ via Agrobacterium-mediated genetic transformation. Transgenic tobacco plants (Nicotiana tabacumSR1) with the same gene construct were also produced. In tobacco, the pCsVMV-GUS was highly expressed in all tissues tested such as leaf, stem, petiole, and roots. In transgenic cassava, the pCsVMV-GUS gene was highly expressed in all tissues and most cell types of in vitro plants including leaf, stem, petiole, and fibrous roots. The pCsVMV-GUS gene was also highly expressed in these tissues as well as in tubers of greenhouse grown cassava. High and stable pCsVMV-GUS gene expression wasmaintained over 3 cycles of ratooning under greenhouse conditions, thus showing the absence of undesired gene silencing effects after repeated in vitro subculturing and vegetative propagation. Fromthe high constitutive levels of GUS activity observed, the study concluded that the CsVMV promoter cassette was useful for high-level expression in cassava over repeated cycles of clonal propagation